(untitled) (Human-Computer Interaction Perspectives, 2024)
User interface (UI) prototyping plays a crucial role in the design and development of software applications, allowing designers to visualize design concepts and gather feedback from stakeholders early in the design process. This research paper explores various tools and methods for UI prototyping, highlighting their features, advantages, and limitations. The paper discusses the importance of prototyping in the design process and examines how different tools and methods can be used to create interactive and realistic prototypes. It also discusses best practices for prototyping and how to choose the right tools and methods based on project requirements. The insights provided in this paper aim to help designers and developers enhance their UI prototyping processes and improve the overall user experience of their applications.